Prevalence and Associated Factors of Cesarean Section in Dhulikhel Hospital, Kathmandu University Hospital - Acharya, R.; Singh, B.; Nepal, J.; Thapa, P.; Pandey, C.; Pandey, J.; Shrestha, S.; Khan, A.; Pun, K. D. (Kathmandu University Medical Journal, 2022)
Background The Cesarean Section (CS) is a major obstetric life-saving procedure used to avoid pregnancy and childbirth complications. Cesarean sections are becoming more popular across the world, as well as in Nepal.Objective To assess the prevalence of cesarean section and its associated factors among women in Dhulikhel, Nepal.Method A cross-sectional study was conducted where 1246 pregnant women of age 15-45 years, admitted and delivered in hospital, were selected through purposive sampling technique and interviewed using structured questionnaires in Dhulikhel Hospital, Kathmandu University Hospital, Kavre, Nepal.Result The prevalence of cesarean section among women was 39.7% where the most common indication was previous cesarean section with scar tenderness, 27.9%. Half of the participants, i.e. 50.6%, were primigravida. Majority of women, 97.5% had done their antenatal checkup and among them 74.8% had their checkup in Dhulikhel Hospital, Kathmandu University Hospital. Most of them, i.e.76.2% had emergency cesarean section and 69.5% had primary cesarean section. Women of the age group 30-45 years (AOR=2.23) and women with higher secondary education level (AOR=2.03) were two times more likely to perform cesarean section. Women involved in service (AOR=1.37) and business (AOR=1.23) had greater odds of performing cesarean section than homemakers. Women giving birth to infants weighing 3.51- 5.00 kg were more likely to perform cesarean section (AOR=1.33).Conclusion The prevalence of cesarean section is noticeably high where the educated, employed and higher aged women are more inclined to cesarean section. More obstetric factors could be explored to determine the rise in cesarean section in Nepal which can help in decision making for clinicians.